Development of a Voltage Compensation Type Active SFCL and Its Application for Transient Performance Enhancement of a PMSG-Based Wind Turbine System - Lei Chen; Hongkun Chen; Jun Yang; Huiwen He (Advances in Condensed Matter Physics)
Considering the rapid development of high temperature superconducting (HTS) materials, superconducting power applications have attracted more and more attention in the power industry, particularly for electrical systems including renewable energy. This paper conducts experimental tests on a voltage compensation type active superconducting fault current limiter (SFCL) prototype and explores the SFCL’s application in a permanent-magnet synchronous generator- (PMSG-) based wind turbine system. The SFCL prototype is composed of a three-phase air-core superconducting transformer and a voltage source converter (VSC) integrated with supercapacitor energy storage. According to the commissioning test and the current-limiting test, the SFCL prototype can automatically suppress the fault current and offer a highly controlled compensation voltage in series with the 132 V electrical test system. To expand the application of the active SFCL in a 10 kW class PMSG-based wind turbine system, digital simulations under different fault cases are performed in MATLAB/Simulink. From the demonstrated simulation results, using the active SFCL can help to maintain the power balance, mitigate the voltage-current fluctuation, and improve the wind energy efficiency. The active SFCL can be regarded as a feasible solution to assist the PMSG-based wind turbine system to achieve low-voltage ride-through (LVRT) operation.